Comparative metagenomic analysis reveals rhizosphere microbial community composition and functions help protect grapevines against salt stress - Wang, Bo; Wang, Xicheng; Wang, Zhuangwei; Zhu, Kefeng; Wu, Weimin (Frontiers in Microbiology, 2023)
Soil salinization is a serious abiotic stress for grapevines. The rhizosphere microbiota of plants can help counter the negative effects caused by salt stress, but the distinction between rhizosphere microbes of salt-tolerant and salt-sensitive varieties remains unclear. This study employed metagenomic sequencing to explore the rhizosphere microbial community of grapevine rootstocks 101-14 (salt tolerant) and 5BB (salt sensitive) with or without salt stress. Compared to the control (treated with ddH2O), salt stress induced greater changes in the rhizosphere microbiota of 101-14 than in that of 5BB. The relative abundances of more plant growth-promoting bacteria, including Planctomycetes, Bacteroidetes, Verrucomicrobia, Cyanobacteria, Gemmatimonadetes, Chloroflexi, and Firmicutes, were increased in 101-14 under salt stress, whereas only the relative abundances of four phyla (Actinobacteria, Gemmatimonadetes, Chloroflexi, and Cyanobacteria) were increased in 5BB under salt stress while those of three phyla (Acidobacteria, Verrucomicrobia, and Firmicutes) were depleted. The differentially enriched functions (KEGG level 2) in 101-14 were mainly associated with pathways related to cell motility; folding, sorting, and degradation functions; glycan biosynthesis and metabolism; xenobiotics biodegradation and metabolism; and metabolism of cofactors and vitamins, whereas only the translation function was differentially enriched in 5BB. Under salt stress, the rhizosphere microbiota functions of 101-14 and 5BB differed greatly, especially pathways related to metabolism. Further analysis revealed that pathways associated with sulfur and glutathione metabolism as well as bacterial chemotaxis uniquely enriched in 101-14 under salt stress, which might play vital roles in the mitigation of salt stress on grapevines. In addition, abundance of sulfur cycle genes which participated in assimilatory sulfate reduction (cysNC, cysQ, sat and sir), sulfur reduction (fsr), SOX systems (soxB), sulfur oxidation (sqr), organic sulfur transformation (tpa, mdh, gdh and betC) significantly increased in 101-14 after treated with NaCl, which might help mitigate harmful effect of salt on grapevine. In short, the study findings indicate that both the composition and functions of the rhizosphere microbial community contribute to the enhanced tolerance of some grapevines to salt stress.